2019
DOI: 10.3892/ijmm.2019.4139
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of Scrophularia buergeriana extract against glutamate-induced toxicity in SH-SY5Y cells

Abstract: The aim of this study was to investigate the antioxidant and anti-apoptotic activities, as well as the underlying mechanisms of action, of Scrophularia buergeriana ( S. buergeriana ) extract (SBE) in glutamate-induced SH-SY5Y cell death. The roots of S. buergeriana were extracted with 70% ethanol, and standardized SBE was used in this study. To induce cytotoxicity, the SH-SY5Y cells were exposed to glutamate for 3 h, or pre-treated with SBE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 44 publications
3
52
1
Order By: Relevance
“…It was reported that glutamate at 1-50 mM concentration affected H 2 O 2 synthesis by brain mitochondria and this effect was associated with complex II, a source of superoxide anion formation in mitochondria and was dependent on the mitochondrial potential [31]. We found a non-significant increase in SOD activity which was not consistent with other studies that had reported a decrease with glutamate [18,32]. ROS is converted to less reactive hydrogen peroxide by SOD through the use of copper/zinc or manganese and could play a protective role in neurodegeneration and had been thought to be activated firstly for defense systems against oxidative stress, in neurodegeneration [33].…”
Section: Discussioncontrasting
confidence: 89%
“…It was reported that glutamate at 1-50 mM concentration affected H 2 O 2 synthesis by brain mitochondria and this effect was associated with complex II, a source of superoxide anion formation in mitochondria and was dependent on the mitochondrial potential [31]. We found a non-significant increase in SOD activity which was not consistent with other studies that had reported a decrease with glutamate [18,32]. ROS is converted to less reactive hydrogen peroxide by SOD through the use of copper/zinc or manganese and could play a protective role in neurodegeneration and had been thought to be activated firstly for defense systems against oxidative stress, in neurodegeneration [33].…”
Section: Discussioncontrasting
confidence: 89%
“…In the pathological condition, extensive DNA damage in cells results in PARP1 cleavage (inactive), preventing DNA repair and thereby leading to cell apoptosis or necrosis (Swindall et al, 2013 ; Morales et al, 2014 ). Abnormal PARP1 cleavage has been implicated in many diseases, such as the neurodegenerative diseases including PD (Lee et al, 2013 , 2019 ). Our studies not only provide novel insight into the biological roles of TMEM230 in the PARP1-linked pathway but also provide a TMEM230-induced cell death mechanism underlying PD-linked pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, final stages of cell death in the two cell lines may differ. A contributory role of caspase-3 activity has been observed in many studies in the Glu-induced model of cell death of SH-SY5Y cells [ 62 , 77 , 78 , 79 ]. In this assay, neuron-like SH-SY5Y cells were treated here with 160 mM Glu, which leads to elevation of caspase-3/7 activity.…”
Section: Resultsmentioning
confidence: 99%